PENGARUH GAYA KEPEMIMPINAN, EMPATI DAN MOTIVASI TERHADAP BUDAYA ORGANISASI KEPALA SEKOLAH - Sri Rahaju Supandi (STKIP PGRI Situbondo, 2023)
this study aims to find out whether there is an influence between leadership styles, empathy and motivation on the organizational culture of the principal. Lack of acceptance of new and good values that can change bad behavior patterns for the better, through the influence of organizational culture, leadership style, empathy and motivation. To carry out organizational culture properly will cause high empathy and work motivation. Simultaneously that a leadership style, empathy, high work motivation will be able to improve the work culture of the principal in the organization. To test the hypothetical research, the researcher chose to use quantitative research methods. The processed data was obtained from the results of the questionnaire distributed at SMPN I Panji with a total of 58 correspondents. The types of data required in this study include primary data and secondary data. The data collection technique in this study is to use the Field Research method. Research instruments in the form of questionnaires filled out through the Google Form. The validity test of correlation data includes a normality test and a linearity test. The normality test was performed with the SPSS Version 20 for windows application with the formula One-Sample Kolmogorov-Smirnov Test. The results of the study obtained there is a positive direct influence of leadership style on empathy with a significant path coefficient value of p₂₁ = 0.603. The positive direct influence of leadership style on increasing organizational motivation is indicated by the value of its pathway coefficient which is P₃₁ = 0.852